Tailings Dam Break: The Influence of Slurry with Different Concentrations Downstream - Chen, Xuanyi; Jing, Xiaofei; Chen, Yulong; Pan, Changshu; Wang, Wensong (Frontiers in Earth Science, 2021)
The risk of tailings dam-break disaster is dependent on the type of slurry and its flow characteristics. The flow charac-teristics of slurry surging from tailings dams collapse are directly influenced by grain-size, breach width, slurry concen-tration and surface roughness of gully. Among these parameters, slurry concentration plays the most critical role, but there are few studies on it. This paper focuses on the flow characteristics of slurry with different concentrations, and a series of flume experiments were carried out to obtain the flow characteristics of inundated height, impact force and velocity in 30%, 40%, 50%, and 60% concentrations. The study confirms that the concentration of slurry has a significant influence on the flow characteristics. Through the experimental study, it is observed that with the decreasing of slurry concentration, the impact force and velocity of slurry increased in varying degrees, on the contrary, the flow height elevated with the slurry concentration decreasing. The main reason is that the higher slurry concentration is, the higher static yield stress and viscosity are in varying degrees. The results can provide a detailed understanding of the slurry concentration influence on the flow characteristic, which guide the evacuation time and height of downstream.